Optimalisasi Penatalaksanaan Kegawatan di Ruang Kegawatdaruratan pada Era New Normal - Yarwin Yari; Veronica Yeni Rahmawati; Ernawati Ernawati; Fendy Yesayas; Ayu Lestari; Arizton Putra Jaya; Eni Fatma Sari (Idea Pengabdian Masyarakat, 2021)
Abstract: Since COVID-19 was first discovered in Wuhan, it has caused COVID-19 referral hospitals to be "overwhelmed" including in Indonesia. In patients with confirmed COVID-19 or in patients with suspected COVID-19, the Basic Life Support (BHD) does not need to be postponed. However, there are some principles that must be adapted to keep patients and caregivers safe. The purpose of this community service activity is to increase the knowledge and insight of participants in general regarding emergency management during the COVID-19 pandemic. The method in implementing community service activities is divided into several stages, namely first conducting socialization, conducting webinars, followed by FGD. The result of this activity is that there is an increase in BHD knowledge among emergency room nurses before and after participating in the training. The provision of online BHD knowledge and training has proven to be effective in increasing the knowledge of emergency room nurses